From orchard to opportunity: Building resilient and sustainable horticulture system - Damodaran, T; Singh, Akath (Indian Horticulture, 2026)
The ICAR–Central Institute for Subtropical Horticulture (CISH), Lucknow, is a premier research institute functioning under the Indian Council of Agricultural Research (ICAR), New Delhi. The institute has evolved over decades in response to the scientific, economic, and social needs of fruit growers in the subtropical belt of India. Its genesis, growth, and achievements are closely intertwined with the horticultural heritage of Uttar Pradesh, especially the Kakori–Malihabad region near Lucknow, which has long been celebrated as a cradle of mango cultivation, harbouring more than 30,000 ha of the GI-tagged Dashehari cultivar.